Electromagnetic wave absorbing composite material and preparation method thereof

By combining cyclic Fe3O4 nanoparticles, reduced graphene oxide, and polyaniline, a high-performance cyclic Fe3O4/reduced graphene oxide@polyaniline composite material was prepared. This material overcomes the shortcomings of single-component materials in electromagnetic wave absorption, achieving thin, light, wide, and strong wave absorption performance, and expanding its application in sensing technology and electromagnetic shielding.

CN114284748BActive Publication Date: 2025-01-07SICHUAN UNIVERSITY OF SCIENCE AND ENGINEERING +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202111582924.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-12-22
Publication Date
2025-01-07
Estimated Expiration
2041-12-22

AI Technical Summary

Technical Problem

Existing single-component absorbing materials exhibit narrow absorption bandwidth and poor electromagnetic absorption efficiency, making it difficult to meet the goals of "thin, light, wide, and strong" absorbing materials.

Method used

A composite material of cyclic Fe3O4/reduced graphene oxide@polyaniline was prepared by combining cyclic Fe3O4 nanoparticles, reduced graphene oxide and polyaniline, and controlling the mass ratio of the three to be (1-3):(1-3):(1-3). The synergistic effect of each component was used to improve the microwave absorption performance.

Benefits of technology

It achieves the characteristics of thinness, low density, wide bandwidth and strong wave absorption of composite materials, meeting the requirements of "thin, light, wide bandwidth and strong" wave absorbing materials, and is suitable for fields such as sensing technology, electromagnetic shielding and radar absorption.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114284748B_ABST
    Figure CN114284748B_ABST
Patent Text Reader

Abstract

The present invention provides a composite material and a preparation method and application thereof. The composite material comprises a ring-shaped Fe 3 O 4 Nanoparticles, coated ring Fe 3 O 4 The reduced graphene oxide and the ring-shaped Fe 3 O 4 The polyaniline in the pores. 3 O 4 The composite material of reduced graphene oxide and polyaniline has the characteristics of thin thickness, low density, wide frequency band and strong absorption. The preparation method of the composite material provided by the present invention has the characteristics of being simple and fast, having few influencing factors, being easy to control, and being safe and environmentally friendly.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of wave absorbing materials, and in particular to a preparation method and application of a composite material; more particularly, to a ring-shaped Fe3O4 / reduced graphene oxide@polyaniline composite material and a preparation method and application thereof. Background Art

[0002] With the rapid development of modern electronic technology and the widespread application of electronic products, wireless communication equipment has become an indispensable part of people's lives, but the problems caused by it, such as electromagnetic interference, electromagnetic information leakage, and electromagnetic radiation pollution, cannot be ignored. Especially with the development of electronic technology towards miniaturization, integration, and high frequency, the above problems are becoming more and more prominent.

[0003] Absorbing materials are materials that can absorb or transform electromagnetic waves projected onto the surface of the material, thereby reducing the energy of the reflected waves. Absorbing materials can reduce electromagnetic pollution and avoid interference between communication lines. Therefore, how to develop and optimize the performance of absorbing materials to make them thin, low-density, wide-band and strong in absorption has become an important topic.

[0004] As a ferrite material with excellent physical and chemical properties, Fe3O4 has important applications in many fields such as pigments, photocatalysts, and electromagnetic wave absorption. In particular, the superparamagnetism, small size effect, and quantum tunneling effect exhibited by nano-Fe3O4 have made nano-Fe3O4 materials attract much attention. Graphene is a new carbonaceous material composed of a single layer of carbon atoms. Adjacent carbon atoms are bonded by sp2 hybridization. Its unique two-dimensional structure gives it high electronic conductivity, good thermal stability, excellent mechanical strength, high dielectric constant, and low density. However, the high conductivity and electromagnetic parameters of pure reduced graphene oxide (rGO) cannot meet the requirements of impedance matching. Polyaniline has broad application prospects in the field of absorbing materials because of its low cost, easy synthesis, high conductivity after doping, excellent chemical and electrochemical redox reversibility, and good environmental stability.

[0005] However, the relatively narrow absorption bandwidth and poor electromagnetic absorption efficiency exhibited by the above-mentioned single-component materials severely limit their application, and there is still a certain gap between their ultimate goal of electromagnetic absorbing materials: "thin, light, wide and strong". Summary of the invention

[0006] In view of the above-mentioned defects existing in the prior art, the present invention provides a composite material having the characteristics of thin thickness, low density, wide frequency band, strong wave absorption, etc.

[0007] The present invention also provides a method for preparing a composite material, by simply compounding single-component materials with general absorbing properties, the obtained composite material meets the requirements of "thin, light, wide and strong" for absorbing materials.

[0008] The present invention also provides application of the composite material in the field of electromagnetic wave absorption.

[0009] To achieve the above object, the first aspect of the present invention provides a composite material, which includes annular Fe3O4 nanoparticles, reduced graphene oxide covering the annular Fe3O4, and polyaniline located in the pores of the annular Fe3O4. By compounding the above three materials, the performance of the obtained annular Fe3O4 / reduced graphene oxide@polyaniline composite material can be better than that of each single component material.

[0010] It is not difficult to understand that by controlling the mass ratio between the single components in the above composite material, the wave absorption performance of the composite material can be further improved. Specifically, the mass ratio of the single components in the above composite material can be controlled by controlling the raw material ratio of the composite material. In the specific implementation process, the solid product is obtained by mixing and reacting the cyclic Fe3O4 nanoparticles, graphene oxide and polyaniline (PANI) as raw materials (i.e., reaction components) in a medium, wherein the mass ratio of the cyclic Fe3O4 nanoparticles, graphene oxide and polyaniline is controlled at (1-3): (1-3): (1-3), and can be especially controlled at (1-3): 1: (1-3), that is, among the three raw materials, the mass of the cyclic Fe3O4 nanoparticles and polyaniline is not less than the mass of graphene oxide. For example, the mass of the above three raw materials is the same, or the mass ratio of the three is 2:1:2, 3:1:2, 2:1:3, etc.

[0011] In a specific implementation process, the average particle size of the composite material is 180nm to 250nm.

[0012] A second aspect of the present invention provides a method for preparing a composite material, comprising the following steps:

[0013] Annular Fe3O4 nanoparticles, graphene oxide and polyaniline are mixed and reacted in a medium, the obtained reaction product is separated into solid and liquid, and the solid product is dried to obtain a composite material, more specifically, an annular Fe3O4 / reduced graphene oxide@polyaniline composite material.

[0014] Among them, the mass ratio of the above-mentioned cyclic Fe3O4 nanoparticles, graphene oxide and polyaniline can be specifically controlled at (1~3): (1~3): (1~3), such as (1~3): 1: (1~3). The above-mentioned medium is used to achieve sufficient mixing between the three reaction components of cyclic Fe3O4 nanoparticles, graphene oxide and polyaniline, and provide a reaction site for the three. In the specific implementation process, the above-mentioned medium is usually water and an organic solvent that is easily soluble in water. For example, the cyclic Fe3O4 nanoparticles and polyaniline can be first ultrasonically dispersed in anhydrous ethanol, and then mixed with a graphene oxide (GO) aqueous solution, and continuously stirred vigorously during the reaction. Of course, the above-mentioned ethanol can also be replaced by other organic solvents that are easily soluble in water, as long as they can assist in dispersion and ensure the smooth progress of the reaction.

[0015] Specifically, the reaction temperature can be controlled within the range of 10°C to 30.0°C, such as reacting at 22°C to 25°C. Vigorous stirring should be maintained during the reaction to ensure sufficient reaction and obtain a reaction product with uniform particle size. The reaction time is preferably not less than 1 hour, such as 1 hour to 5 hours. In the specific implementation process, the reaction time can be controlled within 3 hours to 5 hours to ensure sufficient reaction while avoiding a waste of time due to a long reaction cycle.

[0016] After the reaction is completed, the reaction product is collected and solid-liquid separation is performed to obtain a solid product. The present invention does not specifically limit the specific method of solid-liquid separation, and can adopt magnetic separation, centrifugal separation, or any other feasible solid-liquid separation means.

[0017] The solid product is dried to obtain the final product, i.e., the annular Fe3O4 / reduced graphene oxide@polyaniline composite material. The present embodiment does not particularly limit the specific drying method, as long as the moisture and organic solvent carried in the solid product are fully removed. Generally, vacuum drying, heating drying, and vacuum heating drying can be used. In the specific implementation process, the solid product is placed in a constant temperature drying oven and dried at a temperature of about 70°C for about 12 hours to completely remove the moisture and organic solvent therein to obtain the final product.

[0018] As one of the reaction raw materials, the average particle size of the above-mentioned annular Fe3O4 nanoparticles is basically consistent with the particle size of the composite material, or in other words, the particle size of the composite material mainly depends on the particle size of the annular Fe3O4 nanoparticles. That is, the average particle size of the annular Fe3O4 nanoparticles is also 180nm to 250nm, and it is observed under SEM to be a hollow annular structure with approximately columnar pores. In the specific embodiment process, the above-mentioned annular Fe3O4 nanoparticles are prepared by a process including the following steps:

[0019] In a mixed gas atmosphere of hydrogen and inert gas, α-Fe2O3 is heated to 340°C to 400°C and kept at this temperature for at least 4 hours, and then annular Fe3O4 nanoparticles are obtained after cooling.

[0020] It is easy to understand that the above-mentioned mixed gas is used to provide a reducing atmosphere for the partial reduction reaction of α-Fe2O3 and isolate the air in the environment to prevent the oxygen in the air from reacting with the Fe3O4 ferrite obtained by the reduction reaction. The inert gas may be argon, for example; the volume percentage of hydrogen in the mixed gas is preferably controlled within the range of 6% to 10% to ensure that the Fe3O4 ferrite is obtained and the obtained product has an ideal morphology.

[0021] In the specific implementation process, the ground α-Fe2O3 powder is placed in a crucible, and then the crucible is placed in a tubular furnace, heated to 340°C to 400°C in an atmosphere of a mixed gas of hydrogen and argon, and kept warm for a period of time, such as 4 to 7 hours; after the tubular furnace is cooled to room temperature, the black powder is collected to obtain ring-shaped Fe3O4 nanoparticles.

[0022] The heating rate during the heating process will also affect the progress of the reaction and the composition of the final product to a certain extent. In the specific implementation process, the heating rate is usually controlled at 3.5°C / min to 5.5°C / min, such as about 5°C / min.

[0023] The raw material α-Fe2O3 for preparing the above-mentioned annular Fe3O4 nanoparticles can be purchased commercially or prepared by oneself. In the specific implementation process, the α-Fe2O3 is synthesized by a hydrothermal method. Specifically, a mixed solution of iron salt, dihydrogen phosphate and sulfate is reacted at 200°C to 250°C. After the reaction is completed, the reaction product is separated into solid and liquid, and the solid product is washed and dried.

[0024] Among them, the iron salt used in the preparation of α-Fe2O3 can be ferric chloride (generally ferric chloride hexahydrate), ferric sulfate, etc.; dihydrogen phosphate can be sodium dihydrogen phosphate, potassium dihydrogen phosphate, etc.; the sulfate can be sodium sulfate, potassium sulfate, etc. Specifically, ferric chloride hexahydrate, sodium dihydrogen phosphate and sodium sulfate can be dissolved in deionized water, and stirred thoroughly to form a mixed solution; the mixed solution is transferred to a volumetric flask, shaken to a constant volume; the mixed solution after constant volume is transferred to a reactor, heated to about 220°C, reacted for about 48 hours, and a reaction product is obtained; the obtained reaction product is separated from the solid and liquid, and the solid product is washed and dried to obtain α-Fe2O3.

[0025] Reasonable control of the ratio between the above iron salt, dihydrogen phosphate and sulfate is conducive to the full reaction of the three. In the specific implementation process, the mass ratio of ferric chloride hexahydrate, sodium dihydrogen phosphate and sodium sulfate is (208-212): (0.8-1.2): (1-5), for example 210:1:3.

[0026] After the reaction is completed, the solid product is washed 3 to 4 times with deionized water and anhydrous ethanol, and the washed solid product is placed in a constant temperature box and dried at a temperature of about 70° C. for 12 hours. After grinding, α-Fe2O3 powder can be obtained.

[0027] In the present invention, the above graphene oxide raw material can be prepared by itself or purchased commercially. In the specific implementation process, the graphene oxide raw material used is a commercially purchased graphene oxide solution with a concentration of 4 mg / mL.

[0028] In the present invention, the polyaniline raw material can be prepared by itself, specifically by conventional techniques. In the specific implementation process, the polyaniline used is prepared by chemical oxidation polymerization. Specifically, in an acidic medium, persulfate or dichromate is used as an oxidant to cause aniline monomer to undergo oxidative coupling polymerization.

[0029] In the specific implementation process of the present invention, polyaniline is prepared by the following process (wherein S10-S40 are only used to distinguish different process steps and do not represent the specific operation sequence):

[0030] S10, measuring aniline and hydrochloric acid solution into a three-necked flask, wherein the volume ratio of aniline to hydrochloric acid solution is (1-2):10;

[0031] S20, dissolving ammonium persulfate in deionized water and stirring to form an ammonium persulfate solution, wherein the mass ratio of ammonium persulfate to aniline is (2-2.5):1;

[0032] S30, adding the ammonium persulfate solution into a three-necked flask, stirring to fully mix the ammonium sulfate solution, aniline, and hydrochloric acid solution to obtain a mixed solution, and then reacting the mixed solution at 5 to 10° C. for 1 to 2 hours;

[0033] S40, after the reaction is completed, the obtained reaction product is washed with deionized water and methanol for 2 to 3 times respectively, and then the washed product is dried at a temperature of about 80° C. for about 5 hours to obtain polyaniline.

[0034] The third aspect of the present invention provides application of the composite material in the field of wave absorption.

[0035] The composite material provided by the present invention is obtained by compounding annular Fe3O4 nanoparticles, graphene oxide and polyaniline, so that the performance of the obtained annular Fe3O4 / reduced graphene oxide@polyaniline composite material is better than that of each single component raw material. The maximum reflection loss of the composite material can reach -40.0dB or less when the thickness is 1.5mm-4.2mm, and the bandwidth less than -10dB is above 2.5GHz, and can even reach above 3.5GHz, showing good electromagnetic loss matching characteristics and wave absorption performance, achieving the ultimate goal of "thin, light, wide and strong", so it has broad application prospects in wave absorption fields such as sensor technology, electromagnetic shielding and radar absorption.

[0036] The preparation method of the composite material provided by the present invention can obtain the above-mentioned cyclic Fe3O4 / reduced graphene oxide@polyaniline composite material with good wave absorption performance by simply compounding each single component. Even the preparation of raw materials, such as the indirect synthesis of cyclic Fe3O4 ferrite by hydrothermal method and the preparation of polyaniline by chemical oxidation polymerization, the processes involved are relatively simple; at the same time, the organic reagents involved in the reaction process are relatively small, and basically no environmental pollution is caused. Therefore, the preparation method has the characteristics of being simple and fast, having fewer influencing factors, being easy to control, and being environmentally friendly, and is convenient for large-scale promotion and application. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 The XRD spectrum of the annular Fe3O4 / reduced graphene oxide@polyaniline composite material prepared in Example 1 of the present invention;

[0038] Figure 2 and Figure 3 They are respectively SEM photos of the annular Fe3O4 / reduced graphene oxide@polyaniline composite material prepared in Example 1 of the present invention at different magnifications;

[0039] Figure 4 This is a reflection loss diagram of the annular Fe3O4 / reduced graphene oxide@polyaniline composite material prepared in Example 1 of the present invention;

[0040] Figure 5 This is a reflection loss diagram of the annular Fe3O4 / reduced graphene oxide@polyaniline composite material prepared in Example 2 of the present invention;

[0041] Figure 6 This is a reflection loss diagram of the annular Fe3O4 / reduced graphene oxide@polyaniline composite material prepared in Example 3 of the present invention;

[0042] Figure 7 This is a reflection loss diagram of the annular Fe3O4 / reduced graphene oxide@polyaniline composite material prepared in Example 4 of the present invention;

[0043] Figure 8 This is a reflection loss diagram of the annular Fe3O4 / reduced graphene oxide@polyaniline composite material prepared in Example 5 of the present invention. DETAILED DESCRIPTION

[0044] The technical solution of the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0045] Example 1

[0046] S1. Preparation of ring-shaped Fe3O4 ferrite

[0047] Dissolve ferric chloride hexahydrate (FeCl3·6H2O), sodium dihydrogen phosphate (NaH2PO4) and sodium sulfate (Na2SO4) in deionized water at a mass ratio of 210:1:3, stir for about 30 minutes to fully mix, and prepare a mixed solution. Transfer the mixed solution to a volumetric flask and shake to volume;

[0048] The fixed volume solution was transferred to a reaction kettle, and the reaction kettle was placed in a thermostat to react at a temperature of about 220° C. for 48 hours to obtain a reaction product;

[0049] The reaction product was collected, and after solid-liquid separation, the solid product was washed three times with deionized water and anhydrous ethanol, and the washed product was placed in a constant temperature box and dried at a temperature of about 70° C. for 12 hours to obtain α-Fe2O3;

[0050] The ground α-Fe2O3 powder is transferred to a crucible, and then the crucible is placed in a tubular furnace, H2 and Ar are introduced into the tubular furnace, and the mixture is heated to 360°C at a heating rate of 5°C / min and kept warm for 5 hours, wherein the H2 / (H2+Ar) is about 8%. After the tubular furnace is cooled to room temperature, the black powder is collected to obtain a ring-shaped Fe3O4 ferrite material.

[0051] S2. Preparation of polyaniline

[0052] Measure aniline and hydrochloric acid solution into a three-necked flask and mix them evenly, wherein the volume ratio of aniline to hydrochloric acid solution is 1.5:10;

[0053] Dissolve ammonium persulfate in deionized water and stir thoroughly to obtain an ammonium persulfate solution, wherein the mass ratio of ammonium persulfate to aniline is 2:1, then add the ammonium persulfate solution into a three-necked flask and stir thoroughly to obtain a mixed solution;

[0054] The mixed solution was reacted at a temperature of about 8.0° C. for 1 hour. After the reaction was completed, the reaction product was collected, and the obtained reactant was washed with deionized water and methanol three times each, and dried at 80° C. for 5 hours to obtain polyaniline.

[0055] S3. Preparation of composite materials

[0056] The cyclic Fe3O4 ferrite material obtained in step S1 and the polyaniline powder obtained in step S2 are added to ethanol for ultrasonic dispersion, and then a graphene oxide aqueous solution with a concentration of 4 mg / mL is added, wherein the mass ratio of the cyclic Fe3O4, graphene oxide and polyaniline is 2:1:2, and the volume ratio of anhydrous ethanol and the graphene oxide aqueous solution is about 2:1. After ultrasonic dispersion, stirring is continued for 3 hours, and then the reaction product is magnetically separated to obtain a black product; the black product is dried in a drying oven at 70°C for 12 hours to obtain a final product.

[0057] Figure 1 is the XRD spectrum of the above final product. Figure 1 As shown in the figure, characteristic peaks appear at 2θ of 30.2°, 35.7°, 43.2°, 57.2°, and 62.8°, corresponding to the (220), (311), (400), (511), and (440) crystal planes of Fe3O4, respectively, and match the characteristic peaks of the Fe3O4 (PDF#19-0629) standard card. In addition, a new weak diffraction peak appears near 20.0°, which is attributed to polyaniline and reduced graphene oxide. These results confirm the formation of Fe3O4 / redox graphene@polyaniline nanocomposites; it is speculated that it should be due to the presence of Fe in Fe3O4. 2+ It has reducing properties, so graphene oxide can be reduced to reduced graphene oxide; in addition, a large amount of hydrochloric acid is used in the preparation of polyaniline, so the prepared polyaniline may have strong acidity, so it is easier to reduce graphene oxide to obtain reduced graphene oxide.

[0058] Figure 2 and Figure 3 The SEM photos of the above-mentioned final product at different magnifications are shown in FIG. Figure 2 and Figure 3 Ring-shaped particles with uniform size, uniform dispersion and good crystallinity can be observed, and the particle size of the ring-shaped particles is concentrated in the range of 180nm to 250nm. It is speculated that the ring-shaped particles are ring-shaped Fe3O4, which is coated with a thin layer on the outside, which is speculated to be a thin layer of reduced graphene oxide.

[0059] Based on the above XRD spectra and SEM photos, it can be determined that the preparation method of this embodiment is used to successfully compound the annular Fe3O4, graphene oxide and polyaniline, wherein the annular Fe3O4 is filled with polyaniline and the annular Fe3O4 is covered by a thin layer of reduced graphene oxide.

[0060] Figure 4 This is the reflection loss diagram of the annular Fe3O4 / reduced graphene oxide@polyaniline composite material prepared in this example. Figure 4 It can be seen that under the condition of a thickness of 1.7 mm, the maximum reflection loss of -42.0 dB is reached at 13.8 GHz; the effective absorption bandwidth below -10 dB is 3.7 GHz (12.0 GHz to 15.7 GHz).

[0061] Example 2

[0062] This embodiment provides a ring-shaped Fe3O4 / reduced graphene oxide@polyaniline composite material, and its preparation process is basically the same as that of embodiment 1, except that step S3:

[0063] Annular Fe3O4 and polyaniline powder were added to ethanol and mixed thoroughly, and then graphene oxide solution was added, wherein the masses of Annular Fe3O4, polyaniline powder and graphene oxide were the same. After ultrasonic dispersion, stirring was continued for 3 hours, and then the mixed solution after the reaction was centrifuged to obtain a black product, and the black product was dried in a drying oven at 70°C for 12 hours to obtain an annular Fe3O4 / reduced graphene oxide@polyaniline composite material.

[0064] Depend on Figure 5 It can be seen that under the condition of a thickness of 3.8 mm, the maximum reflection loss of -42.1 dB is reached at 7.5 GHz; the effective absorption bandwidth below -10 dB is 3.6 GHz (5.7 GHz to 9.3 GHz).

[0065] Example 3

[0066] This embodiment provides a ring-shaped Fe3O4 / reduced graphene oxide@polyaniline composite material, and its preparation process is basically the same as that of embodiment 1, except that step S3:

[0067] Annular Fe3O4 and polyaniline powders were added to ethanol and mixed thoroughly, and then graphene oxide solution was added, wherein the mass ratio of Annular Fe3O4, graphene oxide and polyaniline powders was 2:1:2. After ultrasonic dispersion, stirring was continued for 5 hours, and then the mixed solution after the reaction was centrifuged to obtain a black product, which was dried in a drying oven at 70°C for 12 hours to obtain an annular Fe3O4 / reduced graphene oxide@polyaniline composite material.

[0068] Depend on Figure 6 It can be seen that under the condition of 2.6mm thickness, the maximum reflection loss reaches -50.3dB at 9.9GHz. The effective absorption bandwidth below -10dB is 3.3GHz (8.3GHz~11.6GHz)

[0069] Example 4

[0070] This embodiment provides a ring-shaped Fe3O4 / reduced graphene oxide@polyaniline composite material, and its preparation process is basically the same as that of embodiment 1, except that step S3:

[0071] The cyclic Fe3O4 and polyaniline powders were added to ethanol and mixed thoroughly, and then the graphene oxide solution was added, wherein the mass ratio of cyclic Fe3O4, graphene oxide, and polyaniline was 3:1:2. After ultrasonic dispersion, the mixture was stirred for 3 hours, and then the mixed solution after the reaction was centrifuged to obtain a black product, which was dried in a drying oven at 70°C for 12 hours to obtain a cyclic Fe3O4 / reduced graphene oxide@polyaniline composite material.

[0072] Depend on Figure 7 It can be seen that under the condition of a thickness of 4.2 mm, the maximum reflection loss of -51.5 dB is reached at 6.3 GHz; the effective absorption bandwidth below -10 dB is 2.7 GHz (5.0 GHz to 7.7 GHz).

[0073] Example 5

[0074] This embodiment provides a ring-shaped Fe3O4 / reduced graphene oxide@polyaniline composite material, and its preparation process is basically the same as that of embodiment 1, except that step S3:

[0075] The cyclic Fe3O4 and polyaniline powders were added to ethanol and mixed thoroughly, and then the graphene oxide solution was added, wherein the mass ratio of cyclic Fe3O4, graphene oxide, and polyaniline was 2:1:3. After ultrasonic dispersion, the mixture was stirred for 3 hours, and then the mixed solution after the reaction was centrifuged to obtain a black product, which was dried in a drying oven at 70°C for 12 hours to obtain a cyclic Fe3O4 / reduced graphene oxide@polyaniline composite material.

[0076] Depend on Figure 8 It can be seen that under the condition of a thickness of 3.3 mm, the maximum reflection loss of -44.6 dB is reached at 8.0 GHz; the effective absorption bandwidth below -10 dB is 2.8 GHz (6.6 GHz to 9.4 GHz).

[0077] The above is only a preferred specific embodiment of the present invention; however, the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical solution and its improved conception of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. An electromagnetic absorbing composite material, characterized in that: The invention comprises annular Fe3O4 nanoparticles, reduced graphene oxide covering the annular Fe3O4, and polyaniline located in the pores of the annular Fe3O4. The composite material is a solid product obtained by mixing and reacting raw materials including annular Fe3O4 nanoparticles, graphene oxide and polyaniline in a medium, wherein the mass ratio of the annular Fe3O4 nanoparticles, graphene oxide and polyaniline is (1-3): (1-3): (1-3).

2. The electromagnetic absorbing composite material according to claim 1, characterized in that: The average particle size of the composite material is 180nm-250nm.

3. A method for preparing an electromagnetic absorbing composite material, characterized in that: include: Mixing and reacting annular Fe3O4 nanoparticles, graphene oxide and polyaniline in a medium, separating the obtained reaction product into solid and liquid, and drying the solid product to obtain an annular Fe3O4 / reduced graphene oxide@polyaniline composite material, wherein the annular Fe3O4 / reduced graphene oxide@polyaniline composite material comprises annular Fe3O4 nanoparticles, reduced graphene oxide covering the annular Fe3O4, and polyaniline located in the pores of the annular Fe3O4; The mass ratio of the annular Fe3O4 nanoparticles, the graphene oxide and the polyaniline is (1-3): (1-3): (1-3).

4. The preparation method according to claim 3, characterized in that: Furthermore, the reaction temperature is 10°C to 30.0°C, and the reaction time is not less than 1 hour.

5. The preparation method according to claim 3 or 4, characterized in that: The annular Fe3O4 nanoparticles are prepared by a process comprising the following steps: In a mixed gas atmosphere of hydrogen and inert gas, α-Fe2O3 is heated to 340°C to 400°C and kept warm for at least 4 hours, and then cooled to obtain the annular Fe3O4 nanoparticles; wherein the volume proportion of hydrogen in the mixed gas is 6% to 10%.

6. The preparation method according to claim 5, characterized in that: The heating rate is 3.5-5.5°C / min.

7. The preparation method according to claim 5, characterized in that: The α-Fe2O3 is obtained by reacting a mixed solution of iron salt, dihydrogen phosphate and sulfate at 200° C. to 250° C., and separating the reaction product into solid and liquid, washing and drying.

8. The preparation method according to claim 6, characterized in that: The α-Fe2O3 is obtained by reacting a mixed solution of iron salt, dihydrogen phosphate and sulfate at 200° C. to 250° C., and separating the reaction product into solid and liquid, washing and drying.

Citation Information

Patent Citations

  • Method for preparing gamma-ferroso-ferric oxide nano-ring by oxidation process

    CN101264938A

  • Nano-composite wave-absorbing material and preparation method thereof

    CN104448305A